Betaine-Urea Deep Eutectic Solvent Improves Imipenem Antibiotic Activity - Martinez-Gomez, F (Elsevier B.V., 2022)
Beta-lactam antibiotics are highly unstable in aqueous media, which may lead to subclinical concentrations, antimicrobial resistance and therapeutic failure. In previous work we demonstrated that a natural deep eutectic solvent consisting of betaine and urea (BU) is capable of improving the stability of some beta-lactams, including imipenem (IMP), the most unstable antibiotic of the family. Here, IMP-BU was studied by selective protonic Nuclear Overhauser Effect Spectroscopy Magnetic Resonance (H1 NOESY NMR) to gain insight into the mechanism by which BU protects IMP. The kinetics of IMP release and its antibacterial activity were evaluated in diffusional, time-kill and antibiofilm assays. It was found that BU is a protective matrix which allows a fast release of IMP, resulting in superior antibacterial activity when compared to IMP in aqueous solution, both against bacteria growing in planktonic form and in biofilms. Furthermore, it was shown that BU is nontoxic when evaluated in fibroblast primary cell cultures and in organotypic skin cultures, and is not immunogenic when tested in vitro in macrophage cultures, suggesting that BU has potential application as a biomaterial or excipient. © 2022